Effect of pH, temperature and incubation time on cordycepin production from Cordyceps militaris using solid-state fermentation on various substrates. Issue 4 (2nd October 2017) - Adnan, Mohd; Ashraf, Syed Amir; Khan, Saif; Alshammari, Eyad; Awadelkareem, Amir Mahgoub
ABSTRACT: Cordyceps militaris has been a keystone in combating myriad health problems with innumerable far-reaching therapeutic effects. The present study focuses on effect of fermentation conditions such as (pH, temperature and incubation time) and solid-state fermentation (SSF) using solid substrates (wheat, oat and rice) on production of cordycepin. Temperature, pH and incubation time was found to have a direct effect on cordycepin production. The best possible combination of temperature, pH and incubation time was found to be 25°C, 5.5 and 21 days, respectively, for maximum cordycepin production. SSF of solid substrate medium culture leads to the production of cordycepin. Among the solid substrates, rice medium had highest cordycepin production (814.60 mg/g) followed by oat and wheat medium (638.85 and 565.20 mg/g, respectively). This method provides an effective way for increasing the cordycepin production at a large scale. This study could have a wide application in other fermentation processes at industrial level.